2014
DOI: 10.1016/j.jmbbm.2014.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Insights into reference point indentation involving human cortical bone: Sensitivity to tissue anisotropy and mechanical behavior

Abstract: Reference point indentation (RPI) is a microindentation technique involving 20 cycles of loading in “force-control” that can directly assess a patient’s bone tissue properties. Even though preliminary clinical studies indicate a capability for fracture discrimination, little is known about what mechanical behavior the various RPI properties characterize and how these properties relate to traditional mechanical properties of bone. To address this, the present study investigated the sensitivity of RPI properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 52 publications
1
78
0
Order By: Relevance
“…Indentation depth assessed from cRPI on cadaveric femoral bone from 34 donors (65±25 [21–99] yo) was inversely correlated with both peak bending strength and toughness derived from three-point bend (3pt) testing [22]. Similar relationships were observed after conducting cRPI and 3pt testing on femurs from non-diabetic and diabetic rats sacrificed at 32 weeks of age (n=18) as well as on ribs from mature female beagles with and with BP-treatment (n=19) [72].…”
Section: Contribution Of Tissue-level Mechanical Properties To Fractumentioning
confidence: 99%
See 1 more Smart Citation
“…Indentation depth assessed from cRPI on cadaveric femoral bone from 34 donors (65±25 [21–99] yo) was inversely correlated with both peak bending strength and toughness derived from three-point bend (3pt) testing [22]. Similar relationships were observed after conducting cRPI and 3pt testing on femurs from non-diabetic and diabetic rats sacrificed at 32 weeks of age (n=18) as well as on ribs from mature female beagles with and with BP-treatment (n=19) [72].…”
Section: Contribution Of Tissue-level Mechanical Properties To Fractumentioning
confidence: 99%
“…With the BioDent, the periosteal bone is cyclically loaded at 2 Hz between 0 N and a target force, typically 10 N, for 10 to 20 cycles with a load profile similar to nanoindentation (load-to-maximum force, dwell, unload-to 0 N, with each part of the cycle having the same duration of 167 ms). A number of tissue resistance properties can be derived from the resulting force vs. displacement curves (see [22] for details). Whereas the BioDent has a stand to hold the indentation module over the patient’s bone, the OsteoProbe is a hand-held device that generates a one-time, impact load (from 10 N, the triggering force, to ~ 40 N in 0.25 ms) such that the recorded depth of the tip into the bone (150 μm – 260 μm) is indexed to the harmonic mean of multiple indentation depths into a plastic standard (PMMA).…”
Section: Introductionmentioning
confidence: 99%
“…5 These studies show the real potential for this tool in a clinical setting, even while we are only beginning to understand how RPI outcomes compare with properties measured using traditional mechanical testing modalities. [6][7][8][9] The present study is targeted at a more fundamental level than the clinical and preclinical assessments of RPI described above. Rodents are the most common animals used in skeletal research, owing in large part to the biological tools (for example, genetic manipulation) available for these taxa.…”
Section: Introductionmentioning
confidence: 99%
“…Recent study has also demonstrated that microindentation on the bone surface, cause micro-fractures and the analysis of which may be able to correlate with the overall mechanical property of bone tissue. In this method a reference point indentation instrument was used which loads the bone surface at a particular load and frequency and measures the surface mechanical properties (Diez-Perez et al, 2010; Gallant et al, 2013; Granke et al, 2014). Hence possibly use of reference point indentation methods can serve as a new tool for clinical diagnosis of early stages of osteoporotic conditions.…”
Section: Discussionmentioning
confidence: 99%